2003
DOI: 10.1073/pnas.1231012100
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific silencing of dominant disease genes

Abstract: Small interfering RNA (siRNA) holds therapeutic promise for silencing dominantly acting disease genes, particularly if mutant alleles can be targeted selectively. In mammalian cell models we demonstrate that allele-specific silencing of disease genes with siRNA can be achieved by targeting either a linked single-nucleotide polymorphism (SNP) or the disease mutation directly. For a polyglutamine neurodegenerative disorder in which we first determined that selective targeting of the disease-causing CAG repeat is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
297
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(309 citation statements)
references
References 36 publications
7
297
0
1
Order By: Relevance
“…Lowering mutant Htt gene expression in brain may treat HD. In mice, viral vector delivery of short hairpin RNAs (shRNAs) against mutant Htt gene exon 1 or genes that cause other neurodegenerative disorders reduced neuropathology and motor deficits (3)(4)(5)(6)(7)(8)(9)(10). Brain delivery of adeno-associated virus (AAV)-shRNA against mutant Htt improved signs of disease in HD transgenic models (7,11).…”
Section: H Untington's Disease (Hd) Is An Autosomal Dominant Diseasementioning
confidence: 99%
“…Lowering mutant Htt gene expression in brain may treat HD. In mice, viral vector delivery of short hairpin RNAs (shRNAs) against mutant Htt gene exon 1 or genes that cause other neurodegenerative disorders reduced neuropathology and motor deficits (3)(4)(5)(6)(7)(8)(9)(10). Brain delivery of adeno-associated virus (AAV)-shRNA against mutant Htt improved signs of disease in HD transgenic models (7,11).…”
Section: H Untington's Disease (Hd) Is An Autosomal Dominant Diseasementioning
confidence: 99%
“…Several studies have demonstrated the potential of RNA interference (RNAi) based silencing as a therapeutic approach for HD, SCA1, SCA3, SCA6 and SCA7. [2][3][4][5][6][7][8][9][10][11] However, most of these reports have used overexpression models or transgenic animal models to demonstrate efficacy-models which fail to mimic the precise genomic context of mutation found in patients. These models have also failed to provide answers to important questions regarding the necessity and feasibility of allele-specific silencing of the mutant transcript alone, without concomitant silencing of the wild type.…”
Section: Introductionmentioning
confidence: 99%
“…1 Small interfering RNA (siRNAs) are double-stranded RNA molecules first identified as a sequence-specific mRNA-interfering species in C. elegans 2 and plants, 3 and then recognized as a powerful genetic knock-down system in mammalian cells. However, only a few studies have reported successful discrimination between single-nucleotide variants within mRNAs by siRNAs in monogenic dominant disorders, including osteogenesis imperfecta (OI).…”
Section: Introductionmentioning
confidence: 99%